Duplicity Writ Large: A Response to The Silence of Sodom - Hunt, Mary E. (Theology & sexuality, 2002)
Mark D. Jordan's marvellous work reveals the deep layered lies of the Roman Catholic Church. This essay explores the Catholic gay structures of duplicity, the economics of ecclesial injustice and the implications of Professor Jordan's analysis for women. It is an appreciative view that invites further critical reflection on the misogynist dimensions of kyriarchal Catholicism and the gay male welfare system called Catholic theological education.